2010
DOI: 10.1007/s00414-010-0512-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of fibronectin and C5b-9 in the myocardium in cases of carbon monoxide poisoning

Abstract: Even if there is clinical evidence that carbon monoxide poisoning determines cardiac damage, the literature on the cardiac pathomorphology in such cases is scarce. We investigated the immunohistochemical expression of two known markers of fresh cardiac damage, fibronectin and the terminal complement complex C5b-9, in both cardiac ventricles in 26 cases of CO intoxication (study group, 15 ♀, 11 ♂, mean age 47 years, mean COHb level 65.9%, min. 51%, max. 85%) compared to a group of 23 cases of hanging (n = 23, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
(35 reference statements)
2
9
0
1
Order By: Relevance
“…Intrathrombotic PAI-1 expression indicates the thrombus age of ≥3 days. In the previous studies, we demonstrated that neutrophil/macrophage and MMP-9/ MMP-2 ratios in the thrombi could give significant information to estimate the thrombus age [21,22]. In line with these previous studies, uPA/PAI-1 and tPA/PAI-1 were presumed to be more useful for the age estimation of venous thrombi.…”
Section: Discussionsupporting
confidence: 65%
“…Intrathrombotic PAI-1 expression indicates the thrombus age of ≥3 days. In the previous studies, we demonstrated that neutrophil/macrophage and MMP-9/ MMP-2 ratios in the thrombi could give significant information to estimate the thrombus age [21,22]. In line with these previous studies, uPA/PAI-1 and tPA/PAI-1 were presumed to be more useful for the age estimation of venous thrombi.…”
Section: Discussionsupporting
confidence: 65%
“…Such damage is responsible for the right ventricular failure that occurs in cases of pulmonary thromboembolism and severe pulmonary fat embolism. The immunohistochemical markers whose expression was investigated in this study were chosen because they are known to react in cases of early myocardial ischemia, and they allow an easy detection of the damage even in cases of single cell necrosis or of necrosis of little groups of cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, histological alterations in the different phases of wound healing process have been applied to wound age determination [4]. At present, immunohistochemical techniques are widely used in forensic pathological researches [5][6][7][8][9][10][11][12]. Thus, there are lots of immunohistochemical studies on wound age determination [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%